Fragility of a productive space, climate change and flooding in the Bajio, eighteenth century (Tzintzun, Revista de Estudios Históricos, 2016)
The use of historical sources for the reconstruction of climate history is now amethod and a study area fully recognized by modern historiography. The vastinformation in files on catastrophic floods in the Bajio region in addition to provid-ing empirical data on periods of heavy rainfall, yields also information on the useand abuse of certain hydraulic nature farming techniques, particularly floodingirrigation that in the presence of heavy rains caused major floods caused greatersteams of water with the consequent material damage and the unfortunate deathof people. Rapid population growth in the cities of Celaya, Silao, Irapuato andLeon in the eighteenth century, as a concomitant to mining development, gener-ated a significant demand for agricultural products and manufacturers that re-sulted in the expansion of the productive sector and an increasing intensificationof production methods. The multiplication of hydraulic works, both the simplecharacter as complex hydraulic engineering, with its necessary systems of dams,dikes, ditches, streams and puddles deviation of time, eventually had a negativeimpact on the ecosystems of the region causing repeated flooding that destroyedhomes and urban and rural infrastructure, leaving the population unprotected forweeks, months and sometimes years.
Keywords: Climate Change; floods; agriculture; water technology